External shocks and financial imbalances: an interpretation of the Brazilian crisis - Kirsten, Martin Branco; Morrone, Henrique (Brazilian Keynesian Review, 2019)
This paper investigates the causes of the Brazilian recession that began in 2014. If, on the one hand, the conventional diagnosis attributes the crisis to a lack of control of public finances, other interpretations emphasize external shocks and excessive indebtedness of the private sector. The alternative hypothesis is that the deterioration of public accounts is a consequence of the crisis and not its cause. The methodology developed by Toda and Yamamoto (1995) is used to verify the hypothesis of non-causality of Granger between the time series of the balances of the private sector, public sector and current account, from the Central Bank of Brazil (BCB, 2017) for the 2002-2017 period. The results suggest that the balances of the external and private sectors cause in the Granger sense the balance (result) of the public sector.